2022
DOI: 10.1155/2022/4996239
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Idiopathic Membranous Nephropathy for Moderate or Severe Proteinuria: A Systematic Review and Network Meta-Analysis

Abstract: Objective. Numerous studies have demonstrated that the efficacy of drugs differs in idiopathic membranous nephropathy (IMN) patients with moderate or high proteinuria. However, there is no systematic comparison confirming it. This network meta-analysis (NMA) was performed to respectively compare the efficacy of ten IMN treatments in patients with moderate and high proteinuria and compare the risk of adverse events with 10 IMN regimens. Methods. Randomized controlled trials (RCTs) and observational studies anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The optimal immunosuppressive regimen for IMN remains controversial. The effect of tacrolimus [43] and cyclosporine A [44] on remission was relatively better than that of cyclophosphamide, rituximab, and mycophenolate mofetil. Although rituximab was superior in the decline of proteinuria and PLA2R-ab [45], the result was not consistent, and more randomized trials are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal immunosuppressive regimen for IMN remains controversial. The effect of tacrolimus [43] and cyclosporine A [44] on remission was relatively better than that of cyclophosphamide, rituximab, and mycophenolate mofetil. Although rituximab was superior in the decline of proteinuria and PLA2R-ab [45], the result was not consistent, and more randomized trials are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The recently published network meta-analysis partly overcame this limitation. There have been six network meta-analyses in the treatment of IMN, but none of them found significant differences of remission between RTX and CYC (Table 3) [26][27][28][29][30][31]. The network meta-analysis by Zheng et al in 2019 covered 13 immunosuppressive agents in IMN and found that TAC and CYC are superior to other immunosuppressive agents including RTX in terms of total remissions but with no statistical significance [29].…”
Section: Discussionmentioning
confidence: 99%
“…The network meta-analysis by Bose et al in 2022 found that CYC had nonsignificant effects on inducing CR compared with RTX (OR 0.35, CI 0.10-1.24) [31]. Another network meta-analysis by Chen et al in 2022 showed that RTX and steroid + CYC both were better treatments than others for total remissions in patients with proteinuria < 8 g/d [30]. Compared with the above studies, our direct meta-analysis included more studies and came to novel findings on the efficacy in different follow-up periods and antiPLA2Rab levels.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, no statistically significant correlation between the PU level and RTX levels was attained in this, admittedly, rather small study (n=20) (82). Chen et al in their meta-analysis of studies that described the treatment of MN also proved that reduced proteinuria is associated with a better treatment response to RTX (84).…”
Section: Membranous Nephropathymentioning
confidence: 97%
“…Chen et al. in their meta-analysis of studies that described the treatment of MN also proved that reduced proteinuria is associated with a better treatment response to RTX ( 84 ).…”
Section: The Variation In Rtx Pharmacokinetics In Various Glomerular ...mentioning
confidence: 99%